ทัศนคติต่อพฤติกรรมการมีเพศสัมพันธ์ก่อนการสมรส ของนักศึกษามหาวิทยาลัยของรัฐ - นันทกา โรจนวิภาต (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
The objective of this research was to study state university students attitudes on premarital sexual behaviour. The independent variables were sex, age, hometown, family economic status and type of universities, while the attitudes on premarital sexual behaviour was dependent variable. The samples were selected from 400 closed and open university students by using multistage, quota and accidental random sampling method. The data were collected from documentary research, questionnaires and anthropological fieldwork by using in-depth interview from 20 keyinformants. Analysis of data was conducted by using SPSS/PC program to calculate percentage, means, standard deviation and hypotheses testing by chi-square with the level of significance at 0.05. The hypotheses of this research were as follow: 1. Male students had accepted the attitudes on premarital sexual behaviour more than female students. 2. Older students had accepted the attitudes on premarital sexual behaviour more than younger students. 3. Students who lived in Bangkok Metropolis had accepted the attitudes on premarital sexual behaviour more than students who lived in up country. 4. Students with lower family economic status had accepted the attitudes on premarital sexual behaviour more than students with higher family economic status. 5. Open university students had accepted the attitudes on premarital sexual behaviour more than closed university students. The result of research were in accordance with hypotheses number 1, 4, 5 and rejected hypotheses number 2 and 3.